Mitigation Impact of Different Harvest Scenarios of Finnish Forests That Account for Albedo, Aerosols, and Trade-Offs of Carbon Sequestration and Avoided Emissions - Kalliokoski, Tuomo; Bäck, Jaana; Boy, Michael; Kulmala, Markku; Kuusinen, Nea; Mäkelä, Annikki; Minkkinen, Kari; Minunno, Francesco; Paasonen, Pauli; Peltoniemi, Mikko; Taipale, Ditte; Valsta, Lauri; et al. (Frontiers in Forests and Global Change, 2020)
The pressure to increase forest and land carbon stocks simultaneously with increasing forest based biomass harvest for energy and materials emphasizes the need for dedicated analyses of impacts and possible trade-offs between these different mitigation options including also forest related biophysical factors, surface albedo and the formation of biogenic Secondary Organic Aerosols (SOA). We analyzed the change in global radiative forcing (RF) due to changes in these climatic agents as affected by the change in state of Finnish forests under increased or decreased harvest scenarios from a baseline. We also included avoided emissions due to wood material and energy substitution. Increasing harvests from baseline (65% of Current Annual Increment) decreased the total carbon sink (carbon in trees, soil and harvested wood products) at least for 50 years. When we coupled this change in carbon with other biosphere responses, surface albedo and aerosols, decreasing harvests from the baseline produced the largest cooling effect during 50 years. Accounting also for the avoided emissions due to increased wood use, the RF responses of the two lowest harvest scenarios were within uncertainty range. Our results show that the effects of forest management on SOA formation should be included in the analyses trying to deduce the net climate impact of forest use. The inclusion of the rarely considered SOA effects enforces the view that the lower the harvest, the more climatic cooling boreal forests provide. These results should act as a caution mark for policy makers who are emphasizing the increased utilization of forest biomass for short-living products and bioenergy as an efficient measure to mitigate climate change.